Number of medications and polypharmacy are associated with frailty in older adults: results from the Midlife in the United States study - Alqahtani, Bader (Frontiers in Public Health, 2023)
Abstract Objectives: The current study aimed to examine the association between the number of medications, polypharmacy, and frailty in community-dwelling older adults. In addition, the cutoff score for the number of medications related with frailty in this sample was determined. Methods: A cross sectional analyses of Midlife in the United States (MIDUS 2): Biomarker Project, 2004-2009, a multisite longitudinal study, for 328 individuals aged between 65-85 years. Number of prescribed medications was obtained. Polypharmacy was defined as having 5 medications or more. Frailty status was measured using a modified form of Fried frailty phenotype through the presences of the following indicatorsinclude low physical activity; exhaustion; weight loss; slow gait speed and muscle weakness. Multinomial logistic regression model was utilized with relative risk ratio (RRR) and 95% confidence intervals (95% CI) were reported after adjusting for age, sex, BMI, and number of chronic conditions. Receiver operator characteristics and area under the curve were used to determine the cutoff number of medications. Results: Number of medications, and polypharmacy were associated with being frail (RRR: 1.30; 95% CI [1.12, 1.50], p=0.001), (RRR: 4.77; 95% CI [1.69, 13.4], p=0.003), respectively. Number of medications with cutoff 6 medication or more was associated with being in frail category with sensitivity of 62% and specificity of 73%. Conclusion: Polypharmacy was shown to be significantly related to frailty. A cutoff score of 6 or more medications distinguished frail from non-frail. Addressing polypharmacy in the elderly might ameliorate the impact of physical frailty.